Prevalence, Rate and Reasons for Discontinuation of Modern Contraceptives Use among Women Attending Outpatient Clinics at Temeke Regional Referral Hospital, Dar es Salaam (Tanzania Medical Journal, 2023)
BackgroundModern contraceptives use has been the cornerstone towards control of population growth all around the world. In Tanzania there is still a struggle to reach the goals of modern contraceptives use prevalence, and a high percent of unmet need for modern contraceptives. Nevertheless, there is lack of research to show the percent of people who stop using contraceptives, and the reasons for their discontinuation.  ObjectiveTo assess the prevalence, rate and reasons for discontinuation of modern contraceptives use among women aged 15 to 49 years.MethodsThis was a cross-sectional study conducted at Temeke regional referral hospital, in Dar es Salaam, Tanzania. The study population included women of reproductive age (15-49 years old) attending outpatient medical and surgical clinics. A structured questionnaire was used to conduct face to face interview with 247 participants. Convenience non-probability sampling technique was applied. Data analysis was done using SPSS version 20. A p-value of less than 5% was considered statistically significant. Odds ratio with their 95% confidence interval were used to assess the strength of associations between discontinuation of modern contraceptive use and the exposure variables.ResultsThe prevalence of discontinuation was 32%, and the rate of discontinuation was 84.8% in less than 5 years from the beginning of contraceptive use. The individual rates of discontinuation were as follows; implants (31.6%), injectable (22.8%), male condoms (20.2%), intra-uterine devices (17.8%) and oral pills (7.6%). There was no evidence of contraceptive failure. The major reasons for discontinuation of use of contraceptive were to get pregnant (40.5%), experiencing side effects (39.2%), and no known reason accounted for 20.3%.ConclusionThe prevalence of modern contraceptive discontinuation is high and the rate in 5 years-time is also very high. A significant proportion of the population stops contraceptives use without significant reasons, and some because of side effects they experience as a result of contraceptives use. This calls for the need to increase awareness of the public on the possible side effects of contraceptives and how to deal with them.